2020
DOI: 10.1096/fj.201902377rr
|View full text |Cite
|
Sign up to set email alerts
|

Tendon‐derived extracellular matrix induces mesenchymal stem cell tenogenesis via an integrin/transforming growth factor‐β crosstalk‐mediated mechanism

Abstract: Treatment of tendon injuries is challenging. To develop means to augment tendon regeneration, we have previously prepared a soluble, low immunogenic (DNA‐free), tendon extracellular matrix fraction (tECM) by urea extraction of juvenile bovine tendons, which is capable of enhancing transforming growth factor‐β (TGF‐β) mediated tenogenesis in human adipose‐derived stem cells (hASCs). Here, we aimed to elucidate the mechanism of tECM‐driven hASC tenogenic differentiation in vitro, focusing on the integrin and TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 66 publications
3
35
0
Order By: Relevance
“…In these studies, ROCK inhibition resulted in decreased expression of tendon markers and less pronounced tenocyte-like morphology of MSC [20,21]. Indicating a connection between mechanobiology, Rho/ROCK, and the well-described tenogenic effect of TGF-β, more recently, ECM extract-induced tenogenic differentiation was shown to be mediated via integrin as well as TGF-β/Smad pathways [32]. Furthermore, synergistic effects of ROCK activation by surface topography and TGF-β2 on Smad phosphorylation and tenogenic differentiation were reported [33], which is 8 Stem Cells International consistent with similar synergistic effects observed in contexts such as chondrogenic [34] or lung fibroblast differentiation [35].…”
Section: Discussionmentioning
confidence: 90%
“…In these studies, ROCK inhibition resulted in decreased expression of tendon markers and less pronounced tenocyte-like morphology of MSC [20,21]. Indicating a connection between mechanobiology, Rho/ROCK, and the well-described tenogenic effect of TGF-β, more recently, ECM extract-induced tenogenic differentiation was shown to be mediated via integrin as well as TGF-β/Smad pathways [32]. Furthermore, synergistic effects of ROCK activation by surface topography and TGF-β2 on Smad phosphorylation and tenogenic differentiation were reported [33], which is 8 Stem Cells International consistent with similar synergistic effects observed in contexts such as chondrogenic [34] or lung fibroblast differentiation [35].…”
Section: Discussionmentioning
confidence: 90%
“…The KEGG analysis revealed that many signaling pathways were enriched, among which we found the focal adhesion, extracellular matrix (ECM)-receptor interaction, PI3K-Akt and TGF-beta signaling pathways were activated by U0126. These pathways, especially the TGF-beta signaling pathway, have been considered as important factors governing tenogenesis, tendon development, as well as tendon injury healing [ 32 35 ]. GDF6 stood out in our further analysis as it was an important member of TGF- β signaling which was significantly increased by U0126.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is often considered for TL scaffolds since it is an ECM-based biomaterial with excellent bioactivity [ 218 ]. Collagen can be extracted and processed by chemical treatments to form the bioactive scaffolds in TL regeneration.…”
Section: Biopolymers In Commercial Tendon and Ligament Graftsmentioning
confidence: 99%